KEABSAHAN LEGALISASI DOKUMEN ELEKTRONIK PUBLIK (Lex Jurnalica, 2018)
AbstractThe rapid growth of digital technology affects human behavior in fulfilling all aspects especially the document needs. Conventional documents using paper-based media (paper based) gradually shifted into electronic documents that use electronic media (paperless). Now, the need for certification of photocopying fit (legalisir) in accordance with the original documents for public administration services is still needed despite the development of digital technology.However, digital documents are not granted in the form of paper media, stamped and signed by authorized officials or parties such as those conducted on conventional documents. The fact that any printed electronic document issued byauthorized officials has the same legal power as the conventional documents that have been stamped and signed t by them. in society, the dynamics of law showing authenticity of electronic documents still do not show the authenticity of the electronic document itself, for that need to be studied more deeply about the validity of the legalization of electronic documents themselves. Keywords: electronic document, legalization, legalization validityÂ Abstrak Perkembangan teknologi digital yang sangat pesat mempengaruhi prilaku manusia dalam memenuhi semuaaspek terutama kebutuhan dokumen. Dokumen konvensional yang memakai media kertas (paperbased) lambat laun bergeser menjadi dokumen elektronik yang menggunakan media elektronik (paperless). Kebutuhan pengesahan kecocokan fotocopy (legalisasi) sesuai dengan dokumen asliuntuk pelayanan administrasi publik masih diperlukan walaupun perkembangan teknologi digital saat ini. Namun dokumen digital tidak diberikan dalam bentuk media kertas, dicap dan ditandatangani basah oleh pejabat yang berwenang atau pihak yang berkepentingan sebagaimana dilakukan pada dokumen konvensional. Dalam prakteknya setiap hasil cetak dokumen elektronik yang telah diterbitkan oleh pejabat yang berwenang mempunyai kekuatan hukum yang sama dengan dokumen konvensional yang telah dicap dan ditandatangani basah oleh pejabat yang bersangkutan. Ternyata dinamika hukum yang menunjukan keautentikan terhadap dokumen elektronik tersebut masih belum secara holisitik memperlihatkan sistem keautentikan terhadap dokumen elektronik itu sendiri, untuk itu perlu suatu kajian yang lebih mendalam mengenai keabsahan legalisasi dokumen elektronik itu sendiri.Â Kata kunci : dokumen elektronik, legalisasi,keabsahan legalisasi